2020
DOI: 10.18433/jpps30868
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Therapeutic Drug Monitoring to Detect Drug Interaction between Pazopanib and Warfarin: A Case Report

Abstract: Pazopanib is an orally available multi-tyrosine kinase inhibitor and has been used to treat renal cell carcinoma (RCC). Here, we report the case of a patient with RCC with an increased prothrombin time-international normalized ratio (PT-INR) due to pazopanib therapy. In addition, we have reported the change in the blood levels of pazopanib. A 75-year-old man underwent a left nephrectomy for RCC. Four years later, his cancer recurred and pazopanib therapy was initiated. He was also taking warfarin for atrial fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Compared with other drugs, there were fewer dose regulation interventions for pazopanib, which could be because its starting dose was lower than the usual 800 mg and the incidence of adverse events was low. In addition, one case that was useful in discovering the drug interaction confirmed in this study has already been previously reported (47). Recently, Noda et al (34) reported that the effective plasma concentration of pazopanib was in the range of 20.5 to 50.3 µg/mL, and they recommended a dose adjustment to this target range in the future.…”
Section: Discussionsupporting
confidence: 72%
“…Compared with other drugs, there were fewer dose regulation interventions for pazopanib, which could be because its starting dose was lower than the usual 800 mg and the incidence of adverse events was low. In addition, one case that was useful in discovering the drug interaction confirmed in this study has already been previously reported (47). Recently, Noda et al (34) reported that the effective plasma concentration of pazopanib was in the range of 20.5 to 50.3 µg/mL, and they recommended a dose adjustment to this target range in the future.…”
Section: Discussionsupporting
confidence: 72%
“…Conversely, long-term administration of sorafenib and sunitinib for >2 years in patients on HD could be safe and effective without major problems [ 8 ]. Since our TKI clearance findings strongly depended on the individuals from our study, therapeutic drug monitoring for TKIs could be reported to contribute to minimizing AEs [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Pazopanib weakly inhibits the OATP1B1 transport protein, but this inhibition was characterized as having only a low potential for clinically relevant OATP1B1-mediated interactions. 20 Although pazopanib is not capable of inhibiting CYP2C9, warfarin levels may be increased secondary to pazopanib-induced hepatotoxicity, as reported by Takasaki et al 21 This hepatotoxicity is likely caused by the aldehyde metabolite of pazopanib, which reduces the integrity and viability of hepatocytes. [22][23][24] Vanishing bile duct syndrome during pazopanib treatment has also been described.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%